Penerapan Pembelajaran Daring dengan Kurikulum 2013 pada Masa Pandemik COVID-19 di SMA Negeri 1 Nunukan - Fawziah Zahrawati; Indah Indah (IAIN Manado, 2021)
Application of Online Learning with 2013 Curriculum during the COVID-19 Pandemic at SMA Negeri 1 Nunukan. The online learning policy set by the government in an effort to break the chain of spreading the COVID-19 pandemic cannot be separated from various problems. This study aims to determine how the application of online learning with the 2013 curriculum during the COVID-19 pandemic. The research method was descriptive qualitative which was conducted at SMA Negeri 1 Nunukan. The sampling technique was purposive sampling. The data was collected through observation and interviews with teachers as research subjects. After the data was collected, the data was organized, read, classified, interpreted, and then visualized (presented). The results showed that there was a discontinuity in the implementation of the 2013 curriculum in online learning at SMA Negeri 1 Nunukan. This is because some teachers do not have skills in using learning technology, the learning implementation process is not in accordance with the curriculum, and there are constraints on aspects of student assessment. Based on this research, solutions are needed to improve teacher quality and other innovations in learning at SMA Negeri 1 Nunukan